Comparative Analysis of Calculation Methods for Natural Vibration Frequency of Reinforced Soil Retaining Walls - CAI Xiao-guang, CAI Bo-yuan, LI Si-han, HUANG Xin, XU Hong-lu, ZHU Chen (长江科学院院报)
Natural vibration frequency is a crucial parameter in the seismic design of reinforced soil retaining walls. To date, there is no consensus on the calculation methods for the natural vibration frequency of non-monolithic reinforced soil retaining walls. This paper reviews seven existing methods for calculating the natural vibration frequency. Taking the modular reinforced soil retaining wall (hereinafter referred to as the modular type) and the composite gabion geogrid reinforced soil retaining wall (hereinafter referred to as the composite type) as research subjects, we assess the effectiveness of these existing calculation methods by comparing the accuracy coefficient and the absolute percentage error between the measured and calculated results. The analysis reveals that the natural vibration frequencies of the modular and composite models are generally consistent at different heights. Wu Yongsheng’s calculation method shows the closest agreement with the actual measurements. Ghanbari’s method can more effectively mitigate the influence of parameter changes on the analytical calculation, thus demonstrating stronger adaptability. Xu Peng’s method has certain advantages in terms of accuracy and adaptability, with a wider application scope. In seismic design, we recommend that engineers evaluate the natural vibration frequency of the reinforced soil retaining wall before and after construction and consider the horizontal displacement of the panels as an indicator to measure the structural damage state.